Deformation and movement characteristics of debris flow landslide: A case study of the Shaziba landslide in Enshi, China - Zijian SHI; Wen CHEN; Yifan SHENG; Guangli XU (Shuiwen dizhi gongcheng dizhi)
Debris flow landslides usually exhibit high sliding speed and long-distance slip, and their unstable slide is easy to cause serious damage to the surrounding area and significant property loss. On July 21, 2020, under the continuous influence of heavy rainfall, the Shaziba landslide in Enshi lost stability and transformed into a debris flow landslide, ultimately depositing within the Qing River, forming a dammed lake. To explore its kinematic features, such as velocity and displacement, during the Shaziba landslide’s sliding process and the evolving patterns of the landslide mass, a three-dimensional numerical model of the landslide was constructed using high-precision ortho-images obtained from unmanned aerial vehicles (drones). The parameters of the model were calibrated based on the mechanical properties of the landslide mass obtained from laboratory tests. Finally, the Particle Flow Code (PFC3D) software was used to simulate the process of the Shaziba debris flow landslide from sliding to deposition. It is determined that the movement time of the landslide was approximately 757 seconds, with a maximum average velocity of 4.9 m/s, and an average sliding distance of about 960 m. The dynamic process of the landslide can be divided into three stages: unstable sliding (0～18 s), flow propagation (18～331 s), and low-speed deposition (331～757 s). Throughout the sliding process, it exhibited the characteristics of hyper-distance and loss-distance, as well as the volume-increasing effect of debris flow landslides. The deposition pattern of the landslide mass in the Qing River displayed a conical accumulation shape, with thick accumulation near the landslide exit and thin accumulation in the opposite direction of the landslide, which closely matched the actual situation. The model effectively reproduces the sliding process of the Shaziba landslide from instability to deposition. This study can provide valuable insights for the prevention and study of geological hazards related to debris flow landslides.